Clumping and X-rays in cool B Supergiants - Bernini Peron, Matheus; Marcolino, Wagner Luiz Ferreira; Sander, Andreas A. C. (Proceedings of the International Astronomical Union, 2023)
B supergiants (BSGs) are evolved objects on the cool end of the line-driven wind regime. Studying their atmospheres provides important insights on the stellar wind physics of these objects and their evolutionary status. So far important features of their spectra, especially in the UV region, could not be reproduced consistently with atmosphere models. This translates directly into problems of our understanding of their wind properties. Here, we present new insights about the BSGs on the cooler side of the Bi-Stability Jump, corresponding to spectral types later than B1. Using UV and optical data, we analysed a sample of Galactic cool BSGs. Including for the first time X-rays and clumping the wind models, we show that the spectra of cool BSGs cannot be explained without X-rays, despite any clear detection of the target stars.